Khảo sát sự biến đổi hàm lượng hypoxanthine và histamine trong tôm sú bảo quản ở 0oC - Tâm, Lê Nhất; Khuê, Đoàn Như; Văn Thi, Trần Thị (Vietnam Journal of Chemistry, 2017)
Hypoxanthine and histamine which have been reported in a lot of researches are the assessing indicators for the quality of seafood and seafood product. In this paper, we present method to specify hypoxanthine at black tiger shrimp (Penaeus monodon) by HPLC device and the results of hypoxanthine and histamine concentrations in shrimp samples stored at 0oC during 10 days. Quantitative method of hypoxanthine by HPLC showed that the linear range from 0.1 ppm to 5.0 ppm, buffer solution phosphate pH = 4.6 is used as mobil phase, diod array detector measured at 248 nm and recovery efficiency = 90.01 %. Hypoxanthine and histamine concentrations increase while shrimp quality decrease according to the storage time from first day to tenth day. Shrimp quality classification based on TCVN-3726-89 standard and on the hypoxanthine and histamine concentrations can be into main three types: special – type 1 – type 2. Keywords. Determination  hypoxanthine, histamine, Penaeus monodon.